The Relationship Between Patient Safety Implementation and Service Quality in the Inpatient Ward of Lanto Daeng Pasewang Regional General Hospital, Jeneponto - Mangindara Mangindara; Hastuti Hastuti; Nismawati Ananda Putri (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
The implementation of patient safety goals is an effort undertaken by hospitals to improve the quality of healthcare services. This implementation is a crucial program that must be carried out to ensure the safety and comfort of patients within the hospital. Patient safety refers to a condition in which patients are free from illnesses or injuries that should not occur, or from diseases that have the potential to cause harm due to the healthcare services provided. There were recorded patient safety incident cases, with 12 Adverse Events (KTD), 1 Near Miss (KNC), and 3 Potential Incidents (KTC) in 2022. In 2023, there were 2 Adverse Events (KTD), 1 Near Miss (KNC), and 4 Potential Incidents (KTC). This study aims to determine the relationship between the implementation of patient safety measures and the quality of inpatient services at RSUD Lanto Daeng Pasewang Jeneponto. The type of research used is quantitative with a cross-sectional study approach. The sample consists of 334 inpatients at RSUD Lanto Daeng Pasewang Jeneponto, determined using Slovin's formula. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis techniques used include univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using multiple linear regression with the help of SPSS software. The results of the study show a significant relationship between service quality and several patient safety indicators, namely: Correct patient identification (p=0.027), Effective communication (p=0.007), Safety of high-alert medications (p=0.027), Correct site, correct procedure, correct patient for surgery (p=0.000), Reduction of patient fall risk (p=0.024). However, there was no significant relationship found regarding the reduction of infection risk due to healthcare-associated conditions (p=0.060). Simultaneously, all indicators showed a significant relationship with the quality of healthcare services (p=0.000). Recommendation: Nurses and hospital management are advised to further enhance the implementation of patient safety goals to achieve better quality of care